Understanding abnormal psychology : clinical and biological perspectives - Ramsden, Pamilla (Los Angeles : SAGE, 2013)
This comprehensive textbook presents a thorough understanding of abnormal psychology with a focus on the integration of psychology, biology and health and is supported by interactive learning features for undergraduate students --
Includes bibliographical references (pages 410-463) and indexes.
Keywords: Psychology, Pathological -- Textbooks; Psychology -- Textbooks; Mental Disorders